Analysis and critical investigation of the financial statements of food sector companies in Thessaly Region (Greece) that were included in the investment development programs the period 2013-2016 - Rigas Ioannis; Theodossiou George; Rigas Nikolaos; Karelakis Christos; Pantos Nikolaos; Goulas Apostolos (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: The aim of this research study is to assess the progress of the food sector companies that received financial aid for investment through the Developmental Laws in the last years (2013-16) of the economic recession in Thessaly Region (Greece), by choosing a random and representative sample of companies. Design/methodology/approach: In order to achieve this goal, financial data was collected which would be able to provide us with information in order to study the evolution of the food industry in Thessaly Region (Greece). The statistical analysis of the data was done with the statistical analysis package IBM SPSS Statistics 23. The descriptive statistics on the distributions and frequency diagrams (Histograms) and normal frequencies curves for the percentages of changes were also calculated. To test the significance of the differences between the mean values of the financial statements items, the method of One-Way Analysis Of Variance (One-Way ANOVA) was used. The same method was used to test the mean values of both the changes in amounts and in their percentages. Findings: In short, we can say that the percentage changes in Total Assets and Equity the time period 2013-16 are small and concentrated around zero. The same period, we have a significant increase in L/M Debt and Sales, except for a few extreme cases, while the percentage changes in Gross Profit and Profit before Tax are limited. The year 2016 there were significant changes in Taxes and Net Profit from AM2005-16. Research limitations/implications: The collection, processing, and analysis of the financial data of the undertakings were limited to the undertakings which have the obligation to publish their financial data. Originality/value: In recent years, very few studies have been carried out on the effectiveness of investment by private companies subsidized by Greek or European Investment Programs.
Keywords: F65; G11; 330; Investment; financial analysis; financial statement items; Food Industry; Thessaly Region (Greece)